2017
DOI: 10.1021/acs.jpcb.7b02886
|View full text |Cite
|
Sign up to set email alerts
|

Using Neutron Reflectometry to Characterize Antimicrobial Protein Surface Coatings

Abstract: Understanding the interaction of adsorbed or covalently immobilized proteins with solid substrates at the molecular level guides the successful design of functionalized surfaces used in biomedical applications. In this report, neutron reflectometry (NR) was used to characterize the structure of surface-attached antimicrobial protein films, with antimicrobial activity assessed using an adaption of the Japanese Industrial Standard Test JIS Z 2801. NR allowed parameters influencing bioactivity to be measured at n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The protein distribution on and in nanoporous materials is thus an important subject to be clarified, and in-situ spectroscopic techniques for protein adsorption have been developed. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The distribution of adsorbate on a single nanoporous particle has been often observed by microspectroscopy techniques. 4,5 For a nanoporous film on a solid substrate, spectroscopic methods utilizing optical interference [6][7][8][9][10][11][12][13][14] and waveguide mode [15][16][17] are available for the in-situ observation of the molecular adsorption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein distribution on and in nanoporous materials is thus an important subject to be clarified, and in-situ spectroscopic techniques for protein adsorption have been developed. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] The distribution of adsorbate on a single nanoporous particle has been often observed by microspectroscopy techniques. 4,5 For a nanoporous film on a solid substrate, spectroscopic methods utilizing optical interference [6][7][8][9][10][11][12][13][14] and waveguide mode [15][16][17] are available for the in-situ observation of the molecular adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…In-situ neutron reflectometry (NR) is one useful technique for structural characterization of an adsorption layer at a solid/ liquid interface. [11][12][13][14] The scattering length densities (SLD) of D2O and H2O are quite different (Table 1), and SLD contrast between materials within the nanoporous film and solvent can be easily tuned by adjusting solvent composition of a D2O/H2O mixture. When NR measurement is performed under a series of D2O/H2O mixtures, simultaneous analysis of reflectivity data obtained for the D2O/H2O mixtures can reduce ambiguities while modeling, and facilitates determination of the structural properties of the adsorption layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that total cell death was not achieved with HM-1 surface immobilization suggests that tethering reduced protein activity, the amount of HM-1 immobilized to the cotton swatches was too low, or particular coupling reactions gave rise to inactive HM-1, i.e., a tethered orientation that hampered activity. To overcome such possibilities, different linkers, the introduction of a spacer such as polyethylene glycol, or specific attachment should improve the activity profile of these HM-1 functionalized surfaces (Akers et al 2017). Moreover, given the observed aggregation and attachment of cells on the fibers because of HM-1 activity (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…While direct anchorage onto desired surfaces is the simplest approach, significant loss of activity is often observed because of surface-induced conformational changes and reduced dynamics once proteins are tethered onto the solid support (Faccio 2018;Mukherjee and Gupta 2015;Xiao et al 2018). Therefore, a linker or spacer is often inserted between the protein and the surface to retain activity of the protein once immobilized on the surface (Akers et al 2017;Balamurugan et al 2008;Gunda et al 2014;Wu et al 2018). Previously, Edwards et al demonstrated the use of citric acid and (3-aminopropyl) triethoxysilane (APTES) as linkers for the immobilization of lysozyme onto cotton surfaces (Edwards et al 2011).…”
Section: Introductionmentioning
confidence: 99%